Shunt Intervention for Possible Idiopathic Normal Pressure Hydrocephalus Improves Patient Outcomes: A Nationwide Hospital-Based Survey in Japan - Nakajima, Madoka; Miyajima, Masakazu; Ogino, Ikuko; Akiba, Chihiro; Kawamura, Kaito; Kurosawa, Michiko; Kuriyama, Nagato; Watanabe, Yoshiyuki; Fukushima, Wakaba; Mori, Etsuro; Kato, Takeo; Sugano, Hidenori; et al. (Frontiers in Neurology, 2018)
Background and purpose: This study aimed to investigate the efficacy of cerebrospinal fluid shunt intervention for idiopathic normal pressure hydrocephalus (iNPH) using data from a nationwide epidemiological survey in Japan. Methods: We conducted a cross-sectional study using data from a nationwide epidemiological survey performed in Japan. Propensity score matching was used to select 874 patients from 1,423 patients aged 60 years, who were diagnosed with iNPH based on clinical guidelines following a hospital visit in 2012. Patients who experienced an improvement of at least 1 modified Rankin Scale (mRS) grade after the intervention were classified as “improved,” while the remaining patients were classified as “non-improved.” In the shunt intervention (n = 437) and non-shunt intervention (n = 437) groups, the differences in mRS grade improvement were analyzed using the Mann-Whitney U test. Finally, we examined subjects in the shunt intervention group (n = 974) to compare the outcomes and complications of ventriculoperitoneal (VP) shunt (n = 417) with lumboperitoneal (LP) shunt (n = 540). Results: We examined subjects with iNPH to compare the non-shunt intervention group to the shunt intervention group following adjustment for age and mRS grade at baseline by propensity score matching (0.31-0.901). The mRS grade (mean [SD]) was found to improve with non–shunt intervention (2.46 [0.88]) and shunt intervention (1.93 [0.93]) (p<0.001) in iNPH patients. The mRS outcome grades and complications in the VP and LP shunt groups were not significantly different between the two groups. Conclusions: In this study, analysis of the efficacy of shunts for possible iNPH conducted in Japan indicated a significant improvement in the mRS grade between baseline and outcome within 1 year, regardless of the surgical technique, and shunt intervention was found to be effective.